La normativa italiana sulla "procreazione medicalmente assistita" e il contesto europeo - Casini, C.; Di Pietro, M.L.; Casini, M. (Medicina e Morale, 2004)
The recent Italian law on the human reproductive technologies becomes part in the European legislative context that, beginning from 80s of XXth century, has seen the diffusion of laws on the matter. In fact, in the last but one decade of the last century, the legislator faced with a completely new, wide asserted in the praxis, and connoted from a technical and not immediately understanding complexity (moreover in continuous evolution) phenomenon. The difficulty to regulate of so packed matter that involves relevant "goods" (meaning of procreation, value of starting human life, meaning of the family) and interests (of the adults to having a son, of the scientists to make research), has pushed the Governments and the Parliaments to avail themselves of "ad hoc" Commissions reports. Therefore, the different laws are compared with the reports of "ad hoc" Commissions, besides examining the essential contents of the several laws on the grounds of a comparative analysis that highliths the points of convergence and divergence. Two interesting tendencies emerge: on one side a pragmatic trend (whose marked expression is the UK Warnock Report and the consequent British legislation), and characterized from the prevalence of the benefit that can be obtained from the recourse to the reproductive technologies to the prejudice of every legal guardianship of the human embryo's rights, seems to prevail. On the other side, a trend is disposed to recognize to the neo-conceived - a living individual pertaining to the human species - the fundamental human rights on the grounds of modern doctrine of the man's rights: right to the life, to the family, to genetic and psychological identity. This is the course undertaken with European documents of 1989, inaugurated, from the legislative point of view, with German legislation (supported by the sessions of the Benda Commission) and confirmed by recent Italian law. This article does not limit itself to a reasoned review of the laws in force, but it offers starting points of reflection beyond a simple legislative comparison.